THE ANTI-HEAT STRESS EFFECTS AND ACUTE TOXICITY TEST OF AN ANTI-HEAT STRESS PRESCRIPTION - J. Xie; X. Zhang; Z. Chen; J. Tang; J. Zhang (Journal of Animal and Plant Sciences, 2012)
The study was conducted to explore the anti-heat stress efficacy of anti-heat stress prescription (AHSP) and to test its safety. Kunming (KM) mice were randomly divided into the control group, the AHSP group, the heat stress (HS) group, and the (AHSP+HS) group. Following 8 days i.g. administration, the HS group and the (AHSP+HS) group were treated with heat stress to the rectal temperature reached 41°C. Blood samples were collected from mice in all four groups to measure the activity of lactate dehydrogenase (LDH), creatine kinase (CK), superoxide dismutase(SOD), and glutathione peroxidase (GSH-Px), and the concentration of lactic acid(LD) and malondialdehyde (MDA) in the plasma. Furthermore, specimens of liver and intestines were prepared to perform paraffin-embedded sectioning and HE staining to observe the structural changes under microscopy. In another experiment, KM mice were randomly divided into the control group and the AHSP group. Animals in the AHSP group were i.g. administered with AHSP at the maximal dose, to observe the acute toxicity response, body weight change, indexes of liver, spleen, and kidneys, and pathological changes of intestines and liver of mice. It showed that compared to the control group, the HS group exhibited significantly higher activities of LDH (P<0.05), CK (P<0.05) and SOD (P<0.01), and concentrations of LD (P<0.05) and MDA (P<0.01), but only slightly higher activity of GSH-Px. In contrast, the (AHSP+HS) group reduced the activities of LDH and CK and the concentrations of LD and MDA, but significantly increased the activity of SOD (P<0.05), and further increased the activity of GSH-Px. Furthermore, HS resulted in structural damage to the liver and intestines, while AHSP reduced the degree of damage caused by HS and to some extent. In addition, during the 14 days acute toxicity test, the mice were normal at every aspect, including body weight, indexes of liver, spleen, and kidneys, and pathological changes of intestines and liver. It concluded that heat stress can enhance the anaerobic respiration to improve the antioxidant activity of the body, but can also cause enzyme release and lipid peroxidation. AHSP can alleviate the damage caused by anaerobic glycolysis during heat stress and enhance the antioxidant activity of the body, and thus can reduce the degree of damage caused by heat stress and protect livers and intestines from thermal damage. Importantly, AHSP cannot cause any obvious acute toxicity response.
Keywords: heat stress; anti-heat stress prescription; radicals; mouse.